A 903-year annual temperature reconstruction for the southeastern Tibetan Plateau from the tree ring widths of Juniperus saltuaria - Shanshan Xu; Chaogang Zheng; Zhiyuan Shang; Zhigang Zhang; Xinggong Kong; Iain Robertson; Zhijun Zhao (Scientific Reports)
Abstract Precisely dated paleoclimatic records are essential for understanding natural and anthropogenic climate influences. Here, an annually resolved absolutely dated Juniperus saltuaria tree ring width chronology from the Haizi mountain, southeastern Tibetan Plateau (TP) was developed. The chronology shows the annual- to decadal-scale paleoclimatic variability of the southeastern TP over the past 903 years (1115–2017 CE). The tree ring widths correlate significantly with mean annual temperature (Tmean). A linear regression model between ring width and Tmean, accounting for 57% of the variance in temperature from 1959 to 2017 CE, was used to reconstruct the past 903 years of Tmean variation in the southeastern TP. The chronology aligns with other temperature records from the TP, Asia, and the Northern Hemisphere (NH), indicating a marked temperature increase since the late twentieth century, with 1998–2017 CE identified as the warmest period. The coldest thirty years occurred in 1115–1145 CE. Solar activity and the Atlantic Multidecadal Oscillation exert notable influences on temperature fluctuations in this region. Superposed epoch analysis indicates that volcanic eruptions had significantly impacted southeastern TP temperatures, causing dramatic cooling for 2–4 years. Our study presents the longest width chronology developed by Juniperus saltuaria to date, offering a long-term perspective on recent climatic shifts across the southeastern TP. This work enhances understanding of historical climate variability, providing critical insights to refine projections of future climate variability.